Relationship between the Talk Test and ventilatory thresholds in well-trained cyclists - Rodriguez-Marroyo, J. A.; Villa, J. G.; Garcia-Lopez, J.; Foster, C. (The Journal of Strength and Conditioning Research, 2013)
The aim of this study was to extend the range of populations where the Talk Test (TT) might be used as a marker of physiologic thresholds. Eighteen highly trained cyclists underwent 2 incremental tests. One test included measurement of respiratory gas exchange to determine the ventilatory (VT) and respiratory compensation thresholds (RCTs). On a separate day, a TT was performed using the same exercise protocol. During TT, subjects read a standard paragraph at the end of each stage. The first stage at which the cyclists could not talk comfortably and could definitely not talk were referred to as the equivocal (EQ) and the negative stages (NEG), respectively. There were no significant differences in workload, heart rate, lactate, and rating of perceived exertion between VT (3.7 ± 0.4 W/kg, 150 ± 10 b/min, 1.6 ± 0.3 mm/L, and 4.1 ± 1.4, respectively) vs. EQ (3.6 ± 0.4 W/kg, 148 ± 12 b/min, 1.3 ± 0.5 mm/L, and 3.8 ± 1.2, respectively) and RCT (5.3 ± 0.4 W/kg, 177 ± 7 b/min, 4.0 ± 0.9 mm/L, and 7.2 ± 1.0, respectively) vs. NEG (5.3 ± 0.5 W/kg, 176 ± 10 b/min, 4.2 ± 1.3 mm/L, and 6.8 ± 1.5, respectively). We found significant relationships (p < 0.01) between VT and EQ and RCT and NEG for workload (r = 0.86 and 0.94, respectively), heart rate (r = 0.79 and 0.92, respectively), and rating of perceived exertion (r = 0.79 and 0.88, respectively). In conclusion, the present study showed that the EQ and NEG stages of TT can be used as a simple and practical surrogate of the VT and RCT in highly trained cyclists.